Spontaneous hip adductor haematoma - Tripon Martin; Riffault Louis; Bronfen Corinne; Laquievre Antoine; Dolet Nathan (Elsevier, 2020)
Idiopathic spontaneus magnus adductor haematoma in children has never been reviewed before in the litterature. The lesion ressembles a soft tissue tumor. In this case, a 7-year-old girl consulted for a 15-day suspected left hip tumor. The symptoms were not specific, making an acurate diagnosis based solely on clinical assessment difficult. An MRI was conducted and revealed the presence of an haematoma. The possiblity of a tumor located in the soft parts was excluded, thus avoiding the need to conduct a biopsy. The treatement depends on the symptoms. The MRI allowed the dating of the haematoma.